Supplementation of Morinda citrifolia waste as bioactive compound on the performances of broiler - I.A.K Bintang; A.P Sinurat; T Purwadaria (Jurnal Ilmu Ternak dan Veteriner, 2007)
A study on the use of dried Morinda citrifolia waste as feed additive in broiler ration was conducted. One hundred day old chicks (doc) were allocated into 4 levels (control; 0.0; 1.2; 2.4 and 4.8 g/kg feed) of M. citrifolia waste with 5 replication. Each replication had 5 birds. The treatments were allocated in a completely randomized design. Variables measured were: feed intake, live weight, feed conversion ratio (FCR), percentages of carcass and internal organs ( liver. gizard, abdominal fat, and thickness of intestine). The results showed that M citrifolia waste supply did not significantly (P>0.05) affect all variables measured, but feed intake of those fed with high levels (4,8 g/kg) of M. citrifolia waste was significantly (P<0.05) lower than those fed with 1.2 g/kg. FCR was significantly (P<0.05 ) lower as compared to the control; 1.2 and 2.4 g/kg. It is concluded that the best treatment was the supplementation of M. citrifolia waste of 4.8 g/kg, this treatment improved feed efficiency by 5% as compared to the control. Key Words: M. citrifolia Waste, Performances, Broiler